(untitled) (Global Journal of Human-Social Science, 2018)
By equating the functionality of regimes to indigenous culture the study explores the causal mechanisms through which cultural conditions institutional outcomes and design Upon review of relevant literature the study opines the confounding role of culture on the nature of institutions cannot be downplayed Building on Almond and Verba s perception of Participant Political Culture it claims democracy in Africa is likely to remain unresponsive and neither can it bring about predetermined outcomes such as developments growth equality equity and the likes It further claims the functionality of any political arrangement is more likely when such arrangement embodies social accepted norms values and beliefs Hence it contends that for democracy to function in Africa there abounds the utmost need for contextual domestication as opposed to the current system of transplantation Consequently democratic values inherent in the dominant indigenous culture as a possible solution to the crisis of governance should not be dismissed While the research does not assents to return to traditionalism it propagates for the contextual domestication of democracy in tandem with prevailing norms and existential political and societal realities across the African continent